Cytology for PD-L1 testing: A systematic review. (March 2020) - Gosney, John R.; Boothman, A.-M.; Ratcliffe, Marianne; Kerr, Keith M.
Highlights: Systematic review evaluating cytology specimens for PD-L1 testing in NSCLC. Of 709 cytology specimens from 7 studies, 92.0 % were evaluable for PD-L1 testing. OPA was 89.7 % between cytology and histology specimens (≥50 % TCs expressing PD-L1). OPA was 88.3 % between cytology and histology specimens (≥1 % TCs expressing PD-L1). No convincing evidence that cytology specimens cannot be used for PD-L1 testing. Abstract: Evaluation of tumoral programmed cell death ligand-1 (PD-L1) expression is standard practice for patients with advanced non-small-cell lung cancer (NSCLC) who may be candidates for treatment targeting the programmed cell death-1 (PD-1)/PD-L1 pathway. Currently, all of the commercially available immunohistochemistry assays have been validated for use with histology specimens although, in routine clinical practice, approximately 30–40 % of patients with advanced NSCLC have only cytology specimens available for diagnosis, staging, and biomarker analysis. This systematic review evaluated the success rate, concordance, and clinical utility of using cytology specimens to assess tumor PD-L1 expression levels compared with histology specimens from patients with advanced NSCLC. EMBASE and PubMed database searches identified 142 unique, relevant publications, of which 15 met the inclusion criteria for at least one analysis. In 709 specimens, across seven publications, the proportion of cytology specimens evaluable for PD-L1 testing was 92.0 %. Among nine studies eligible for concordance analysis between cytology and histology specimens at a PD-L1 tumor cell expression cutoff of ≥50 %, overall percentage agreement was 89.7 % (n = 428), 72.0 % for positive percentage agreement (n = 218), and 95.0 % for negative percentage agreement (n = 258); results using a tumor PD-L1 expression cutoff of ≥1 % were similar. Our analyses suggest that using cytology specimens to assess PD-L1 expression is feasible, with good levels of concordance between cytology and histology specimens using PD-L1 tumor cell expression cutoffs of ≥1 % and ≥50 %. In conclusion, there is no convincing evidence that cytology specimens are inadequate or inferior to histology specimens for assessing PD-L1 expression in patients with NSCLC.